PENGARUH TINGKAT PENDIDIKAN, UPAH, KESEHATAN, DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI BALI - Sutrisna, Ida Bagus Adi; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
The development process is often associated with the industrialization process. One of the key goals of economic development in the industrialization process is to provide sufficient employment to meet the growing labor force, which is growing at a faster rate than employment opportunities. Employment remains a complex phenomenon in Bali. Moreover, the Bali labor market is expected to become more and more integrated in the future. The purpose of this study is to analyze the impact of education, wages, health and investment on employment across districts/cities in Bali. Study locations in districts/cities for this study were determined based on data published by the Central Bureau of Statistics (BPS) using the method of collecting non-participating observational data. The data analysis technique used in this study is multiple regression analysis. The results of this study show that education level, wages, health and investment all affect employment. Diversity in education and investment has negative and significant implications. For wage and health variables, this has a positive but not significant effect.. keyword : Education Level, Wage, Health, Invesment, Employment. Klasifikasi JEL: C68, F43, L52